A decadal decline in relative abundance and a shift in microphytoplankton composition at a long‐term coastal station off southeast Australia. (24th March 2014) - Ajani, Penelope A.; Allen, Andrew P.; Ingleton, Tim; Armand, Leanne
Abstract : In this study, we examined 11 yr (1998–2009) of water samples collected from Port Hacking coastal monitoring station 8 km offshore from Sydney, Australia, to assess changes in the microphytoplankton in relation to climate‐related trends in environmental variables. A total of 152 taxa (85 genera) were identified, with the small diatom Thalassiosira cf. partheneia and the tropical cyanobacterium Trichodesmium erythraeum being the dominant species over the past decade. Taxon richness showed a distinct seasonal pattern, peaking in the austral winter. Ordination analyses revealed significant seasonal and interannual trends in species composition, including a decadal decline in dinoflagellates relative to diatoms toward the present. This decadal shift in taxonomic composition was, in turn, significantly associated with declines in water temperatures over this time period. Total abundance varied by 12 orders of magnitude (8.5 × 10 −8 to 7.4 × 10 4 cells L −1 ), with values separable into bloom and nonbloom regimes at an abundance threshold of 7.1 × 10 −5 cells L −1 . Significant temporal declines in abundance were observed during both bloom and nonbloom regimes. Blooms occurred most consistently in March, September, and December.